Makna Cinta Kasih Sayang pada Video Musik Lagu Kirana-Dewa 19 - Luthfan Wagas Wiratirta; Adrio Kusmareza Adim (Jurnal Komunikasi Nusantara, 2023)
Affection love is an essential basic feeling that you always want to get and give. The Kirana song music video is a communication tool that contains messages and information on the meaning of affection love, which has many followers and unique, so it is necessary to examine the signs. The sign interpretation by constructivist analysis triadic semiotics of Charles Sander Pierce's which is built from primary and secondary data. The results of the research on the kirana song music video have the theme of getting lost in affection love. Affection love in the kirana song music video is represented by a combination of traditional and contemporary symbols. Dewi Kirana in the two dimensions of life is the main sign that represents and is a symbol of affection love. Verbal signs of affection love in the kirana song music video use various poetic language styles. Affection love is needed by every human being and youth is a critical age in trying to get a sense of affection love. Lack of affection love can cause humans to be helpless, directionless and frustrated and encourage negative actions. Affection love can be felt by directing it to positive feelings and controlling emotions. Storyline of kirana song begins with Dewi Kirana falling into a feeling of alienation, stranded in fake affection love and solving problems with negative actions and ends with Dewi Kirana's arrows. Abstrak Cinta kasih sayang suatu rasa dasar hakiki yang selalu ingin didapatkan dan diberikan. Video musik lagu Kirana merupakan salah satu alat komunikasi yang mengandung pesan dan informasi makna cinta kasih sayang yang unik sehingga perlu diteliti makna tanda-tanda yang digunakan. Untuk memaknai tanda dilakukan analisis semiotika triadik Charles Sanders Pierce’s secara konstruktivisme yang dibangun dari data primier dan sekunder. Hasil penelitian video musik lagu kirana mempunyai tema ketersesatan cinta kasih sayang. Cinta kasih sayang dalam video musik lagu Kirana direpresentasikan dengan perpaduan simbol tradisional dan kekinian. Dewi Kirana dalam dua demensi kehidupan adalah tanda utama yang merepresentasikan dan merupakan simbol cinta kasih sayang. Tanda verbal cinta kasih sayang dalam video musik lagu Kirana digunakan berbagai gaya bahasa yang puitis. Cinta kasih sayang sangat dibutuhkan setiap manusia dan remaja adalah usia yang kritis dalam usaha mendapatkan rasa cinta kasih sayang. Kurang rasa cinta kasih sayang dapat menyebabkan manusia tidak berdaya, tidak punya arah dan frustasi serta mendorong melakukan tindakan bersifat negatif. Alur cerita Lagu kirana diawali Dewi Kirana terjun pada rasa terasing, terdampar pada rasa cinta kasih sayang palsu dan pemecahan masalah dengan tindakan negatif dan diakhiri dengan arahan panah Dewi Kirana.